2014
DOI: 10.7860/jcdr/2014/6735.4809
|View full text |Cite
|
Sign up to set email alerts
|

Role of FNAC in the Preoperative Diagnosis of Salivary Gland Lesions

Abstract: intrOductiOnSalivary gland swellings can result from tumours, an inflammatory process or cysts. It can sometimes be difficult to establish as to whether pathology arises from the salivary gland itself or from adjacent structures such as lymph nodes, soft tissues or skin. Fine Needle Aspiration Cytology (FNAC) is a widely used, safe and relatively nontraumatic procedure that can quickly provide important information. The main goal of doing FNAC of salivary gland lesions is to assist clinicians in the management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 11 publications
3
15
0
Order By: Relevance
“…Ziehl-Neelsen stain was done in all cases of granulomatous lymphadenitis but none of them revealed the presence of acid-fast bacilli. [11] reported the rate of sialadenosis as 16.12% (29/180), whereas Fernandes H et al [12] observed the rate of sialadenosis as 9.09% (8/88) and that of cystic lesion as 11.36% (10/88) in their study of 80 patients with salivary gland swellings.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Ziehl-Neelsen stain was done in all cases of granulomatous lymphadenitis but none of them revealed the presence of acid-fast bacilli. [11] reported the rate of sialadenosis as 16.12% (29/180), whereas Fernandes H et al [12] observed the rate of sialadenosis as 9.09% (8/88) and that of cystic lesion as 11.36% (10/88) in their study of 80 patients with salivary gland swellings.…”
Section: Discussionmentioning
confidence: 96%
“…These tumors were further categorized as benign (54.42%) (Figure 2), suspicious for malignancy (1.36%) and malignant (12.92%) ( Figure 3) which is in accordance with Gupta S et al [9] who reported the benign tumor as 54.94% (50/91) and malignant tumor as 15.38% (14/91) in their study, based on salivary gland aspirates from 91 cases. Rate of occurrence of benign tumors in various studies ranged from 29% to 80% and that of malignant tumors from 4.44% to 26.66% [3][4][5][6][9][10][11][12][13][14][15][16][17][18]. Most common benign tumor in the present study was pleomorphic adenoma (90%) with maximum no of cases in 21-40 years age group predominantly affecting the females, with male to female ratio of 1:1.66.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with those of several other studies. 8,[12][13][14][15] Amongst the benign neoplasms, pleomorphic adenoma was most commonly seen and muco-epidermoid carcinoma was the most frequently encountered malignant neoplasm. 3,14,16 Chronic sialadenitis was the most commonly diagnosed lesion of salivary gland.…”
Section: Discussionmentioning
confidence: 99%
“…They consist of parotid, submandibular, sublingual, and the minor glands that are numerous and widely distributed throughout the mouth and oropharynx. [1][2] Salivary gland disorders can arise from infection, inflammation, cystic changes, degenerative process and neoplastic etiologies. [3][4] Most common conditions of salivary gland disease arise from acute infection and inflammation.…”
Section: Introductionmentioning
confidence: 99%